Raising the Bar An Overlooked Element for Identifying a Staurogram within Nomina Sacra - Roth, Dieter T. 1975- (2021)
Recent discussions of the “meta-data” of NT manuscripts have included consideration of the so-called “staurogram” found in some forms of the nomen sacrum for σταυρόω or σταυρός. In several early NT papyri, this tau/rho monogram is clearly visible; however, in certain passages (e.g., in 𝔓⁴⁵, 𝔓⁶⁶, and 𝔓¹²¹), its presence is either not entirely certain or debated. In such instances, the discussion must necessarily appeal to other elements in or features of the manuscript in order to posit the presence or the absence of a staurogram. This brief study considers a heretofore overlooked paleographical feature as evidence for identifying the presence of unclear or disputed instances of a staurogram in nomina sacra , namely the elevated manner in which the attendant supralinear stroke is written.
Keywords: 𝔓¹²¹; 𝔓⁶⁶; 𝔓⁴⁵; Paleography; Nomina Sacra; staurogram